Concealment of Objectivity in Merchandise Within the Study of Hadith Ahkam on Sharia Economy: An Analysis from the Perspective of Shafi’i Scholars - Harahap, Haddad Ulum; Harahap, Rijal Allamah (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2024)
This research aims to examine the views of Shafi’i ulama regarding the concealment of objectivity in merchandise in the context of sharia economics, using an analysis method of the hadith ahkam on sharia economy. This study identifies the views of Shafi’i scholars on the practice of hiding relevant information in business transactions, as well as its theological and practical implications in the modern economic context. This study is library research. The data collection technique used is documentation. The analysis technique used is descriptive qualitative. This study analyses the relevant hadiths to provide an in-depth understanding of how the principles of Islamic economics can be applied in daily business practices. The findings of this research reinforce the importance of transparency, honesty, and objectivity in business transactions according to the views of Shafi’i scholars and provide a significant contribution to the development of contemporary sharia economics. Thus, this research provides valuable insights for business practitioners, academics, and policymakers in understanding Islamic principles in the context of the modern economy. Penelitian ini bertujuan untuk mengkaji pandangan ulama Syafi'i terkait dengan penyembunyian objektivitas pada barang dagangan dalam konteks ekonomi syariah, dengan menggunakan metode analisis terhadap hadis-hadis Ahkam ekonomi syariah. Kajian ini mengidentifikasi pandangan ulama Shafi'i terhadap praktik menyembunyikan informasi relevan dalam transaksi bisnis, serta implikasi teologis dan praktisnya dalam konteks ekonomi modern. Studi ini adalah penelitian pustaka. Teknik pengumpulan data yang digunakan adalah dokumentasi. Adapun teknik analisa yang digunakan adalah diskriptif kualitatif. Studi ini menganalisa hadis-hadis relevan memberikan pemahaman yang mendalam tentang bagaimana prinsip-prinsip ekonomi syariah dapat diaplikasikan dalam praktek bisnis sehari-hari. Temuan dari penelitian ini memperkuat pentingnya transparansi, kejujuran, dan objektivitas dalam transaksi bisnis menurut pandangan ulama Shafi'i, serta memberikan kontribusi yang signifikan dalam pengembangan ekonomi syariah kontemporer. Dengan demikian, penelitian ini memberikan wawasan yang berharga bagi praktisi bisnis, akademisi, dan pengambil kebijakan dalam memahami prinsip-prinsip Islam dalam konteks ekonomi modern.